FUNGSI TARI DALAM UPACARA ADAT NGELETARKEN PADA MASYARAKAT KARO - FRANSISKA C BANGUN (Gesture: Jurnal Seni Tari, 2014)
Abstract The purpose of this study is to discuss about the traditional ceremonies to dispose of pesky ngeletarken a widower, the function of dance and music in traditional ceremonies to dispose of pesky ngeletarken a widower at the Karo people. To discuss this study uses the theories related to topics such as the theory of functions, ceremonial sense, and understanding ngeletarken. When the study was conducted for 2 months ie July to September 2014 was conducted at the research location Pernantin villages, districts Juhar, Karo. The method used to discuss the function of dance in ceremonial ngeletarken in Karo society is a qualitative descriptive method, the population in this study as well sample the peoples in Pernantin,  artists, and cultural figures who know about the function of dance in ceremonial ngeletarken the Karo people. Data collection techniques include library research, observation, interviews, and documentation. Based on the research conducted, it can be described that essentially ceremonial ngeletarken based on the destination and time of traditional ceremonies ngeletarken implementation can be divided into two, namely: to get rid of pesky a widower who had several times a widower since his partner died and implemented during traditional ceremonies nurun- declining (when a partner dies), and to get rid of pesky couple who do not have children or have children just women or men executed during the ceremony nurun-nurun (when the family realized ceremonial cawer metua). Ngeletarken traditional ceremony was held after the core event or after paying the customs debt. Dance and music are supporting elements that must exist. The actors in traditional ceremonies is a person that will ngeletarken diletarken, kalimbubu, child Beru, sukut, musicians, and the audience who attended the ceremonial nurun-nurun. Ngeletarken traditional ceremony will be held in the ceremonial nurun-nurun, while the sequence of the event are: (bronze, sirang-sirang, custom drums, delivering a message, ngeletarken, custom drum continued, dropping bodies, and cover). The essence of traditional ceremonies ngeletarken is trance. Instruments used in traditional ceremonies is a drum telu ngeletarken sendalanen five sada perarih consisting of sarune, singindungi drum, drum singanaki, gung, and penganak. The drum (music accompaniment) is a ceremonial drum simalungen ngeletarken mass is, drum ins, drum Lawes, and drum procession Arak-araki. Keywords: dance and ceremonial functions ngeletarken